Optimal Investment Strategy under Stochastic Interest Rates - Mtunya, Adeline Peter; Ngare, Philip; Nkansah-Gyekye, Yaw (Scientific Research Publishing, 2017)
We study how firms’ management can make effective investment decision under the influence of random interest rates. We define the threshold interest rate value below which investment can be effectively done and above which investment is not optimal. We use a stochastic differential equation with alternating drift to find the optimal investment policy under stochastic interest rate. One of our results indicated that, the optimal condition for investment expansion is when the interest rate is low and the profit level is high. Also, there exists the threshold interest rate value which forms the basis for investment decision of a company. Moreover, we revealed that it is not optimal for the managers to plan for firm’s business expansion when is already making extremely high profits. At the end we were able to confirm that business is generally more stable when the interest rates are lower than those when they are high. Since firms in emerging economies suffer most from interest rate fluctuations, they need more effective investment strategies. Monetary policy makers of such economies need to ensure low interest rates in order to promote firms’ investment and therefore boost the general economy
Keywords: Firm Investment Strategy; Interest Rates; Emerging Market Countries; Stochastic Optimal Control